2011
DOI: 10.1182/blood-2010-11-317909
|View full text |Cite
|
Sign up to set email alerts
|

The ability of MLL to bind RUNX1 and methylate H3K4 at PU.1 regulatory regions is impaired by MDS/AML-associated RUNX1/AML1 mutations

Abstract: The mixed-lineage leukemia (MLL) H3K4 methyltransferase protein, and the heterodimeric RUNX1/CBF␤ transcription factor complex, are critical for definitive and adult hematopoiesis, and both are frequently targeted in human acute leukemia. We identified a physical and functional interaction between RUNX1 (AML1) and MLL and show that both are required to maintain the histone lysine 4 trimethyl mark (H3K4me3) at 2 critical regulatory regions of the AML1 target gene PU. IntroductionThe transcriptional regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 47 publications
2
67
0
Order By: Relevance
“…42 Reducing PU.1 levels can induce AML in mice, 34 and low PU.1 levels have also been implicated mechanistically in specific forms of leukemia such as acute promyelocytic leukemia 43,44 and core-binding factor leukemia ( Figure 5A-C). [8][9][10][11]14 However, the observation that the Runx-PU.1 pathway is essential in HSC biology led us to investigate whether normal and leukemic stem cells might share the requirement of Runx-induced PU.1 for their stemness. As proof of principle, we disrupted the Runx-PU.1 axis in AML/ETO9a-induced leukemia and observed a dramatic decrease in leukemic stem cell function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Reducing PU.1 levels can induce AML in mice, 34 and low PU.1 levels have also been implicated mechanistically in specific forms of leukemia such as acute promyelocytic leukemia 43,44 and core-binding factor leukemia ( Figure 5A-C). [8][9][10][11]14 However, the observation that the Runx-PU.1 pathway is essential in HSC biology led us to investigate whether normal and leukemic stem cells might share the requirement of Runx-induced PU.1 for their stemness. As proof of principle, we disrupted the Runx-PU.1 axis in AML/ETO9a-induced leukemia and observed a dramatic decrease in leukemic stem cell function.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] In leukemia with chromosomal translocations, a dominant negative effect of the fusion protein and inactivation of the Runx downstream target PU.1 has been considered as a critical mechanism of leukemia development. [8][9][10][11][12][13][14][15] Runx1 knockout mice lack definitive hematopoiesis, 16 mainly because of the essential role of Runx1 in the endothelial-tohematopoietic cell transition during embryonic development. [17][18][19][20] However, studies of its function in adult hematopoietic stem cells (HSCs) have been inconsistent, with some demonstrating that Runx1 deficiency results in HSC defects 21,22 and others suggesting minimal impact on HSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Some transcription factors, such as Menin, LEDGF, HCF1/2, E2F, NFE2, p53, and c-Myb, have been shown to interact with MLL family members, which could lead to methylation of H3K4 in a locus-or DNA sequence-specific manner [16,17,[25][26][27][28][29]. A recent study by our group identified a physical and functional interaction between RUNX1 and MLL, and showed that both are required for maintenance of the H3K4me3 mark at two critical regulatory regions of the RUNX1 target gene PU.1 locus [30].…”
Section: Mll and Its Role In Normal Hematopoiesismentioning
confidence: 99%
“…Moreover, RUNX1 binds MLL and methylated H3K4 at PU.1-regulatory regions. RUNX1 mutations impair this interaction resulting in loss of the H3K4me3 mark within PU.1-regulatory regions, and decreased PU.1expression [31].…”
Section:  Functional Properties Of Runx1mentioning
confidence: 99%